Instant jQuery drag-and-drop grids how-to : a practical, hand-on guide to building drag-and-drop layouts using Gridster, jQuery, and CSS /: a practical, hand-on guide to building drag-and-drop layouts using Gridster, jQuery, and CSS. (©2013) - Unknown
No abstract available